Emotion dysregulation and childhood trauma are not significantly associated with NSSI scar cognition among Indonesian emerging adults - Tiara Annisya Ni'am; Rr Dwi Astuti (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Non-Suicidal Self-Injury (NSSI) represents a significant public health issue among emerging adults globally and in Indonesia, heavily framed as a byproduct of emotional and developmental vulnerabilities. Purpose: To examine whether emotion dysregulation and childhood trauma were individually and jointly associated with NSSI scar cognition among Indonesian emerging adults. Method: Utilizing a cross-sectional correlational design. Data were collected online via Google Forms using a purposive sampling technique based on specific inclusion criteria from 105 emerging adults aged 18–30 with a history of NSSI within the last 6 months. Instruments included the Non-Suicidal Self-Injury Scar Cognition Scale (NSSI-SCS), Difficulties in Emotion Regulation Scale–18 (DERS-18), and Childhood Trauma Questionnaire–Short Form (CTQ-SF). Data were analyzed using multiple linear regression and Pearson product-moment correlation. Results: The multiple regression analysis revealed no significant simultaneous relationship between emotion dysregulation, childhood trauma, and NSSI scar cognition (R = 0.117, R² = 0.014, F = 0.712, p = 0.493). Furthermore, no significant relationship was found partially between emotion dysregulation and NSSI (r = 0.070, p = 0.239) or between childhood trauma and NSSI (r = -0.101, p = 0.153), indicating that all proposed hypotheses were not supported. Conclusion: Emotion dysregulation and childhood trauma were not significantly associated with NSSI scar cognition in this sample. These findings should be interpreted cautiously because of the cross-sectional design, nonprobability sampling, and modified measurement instruments.